1998
DOI: 10.1159/000028644
|View full text |Cite
|
Sign up to set email alerts
|

Death in Shunted Hydrocephalic Children in the 1990s

Abstract: Using a combined search of the Children’s Hospital (Birmingham, Ala., USA) medical records and the Jefferson County Health Department death records, we reviewed all shunt-related deaths that occurred between January 1990 and July 1996. Of these, we excluded patients who died of nonhydrocephalus-related reasons, such as bronchopulmonary dysplasia, as well as patients who had other serious neurological illnesses such as brain tumor and hydranencephaly. Twenty-eight patients died of shunt-related causes in the 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 15 publications
2
41
0
Order By: Relevance
“…This is well within the published range in the current literature [9, 10, 11, 12, 22, 26, 29]. We observed a 1.4% mortality rate over the study period, while recent reports suggest a mortality rate of up to 4% may be observed within 36 months in patients with shunted hydrocephalus [30]. Piatt and Carlson [11]report a median shunt survival time of 6 years, whereas 50% of shunts inserted by Liptak and McDonald [10]had failed by 23 months.…”
Section: Discussionsupporting
confidence: 91%
“…This is well within the published range in the current literature [9, 10, 11, 12, 22, 26, 29]. We observed a 1.4% mortality rate over the study period, while recent reports suggest a mortality rate of up to 4% may be observed within 36 months in patients with shunted hydrocephalus [30]. Piatt and Carlson [11]report a median shunt survival time of 6 years, whereas 50% of shunts inserted by Liptak and McDonald [10]had failed by 23 months.…”
Section: Discussionsupporting
confidence: 91%
“…It is accompanied in 80–90% of cases by shunt-dependent hydrocephalus, which accounts for a substantial portion of the long-term morbidity and mortality associated with the disease [1]. Most children with hydrocephalus will require multiple shunt revisions, and shunt dependence carries with it a 1% per year mortality [2]. While improvements in vitamin supplementation and prenatal education and screening are significantly reducing the incidence of myelomeningocele, new cases continue to occur at the rate of 1 per 1,000 live births in high-risk regions of the US [3].…”
Section: Introductionmentioning
confidence: 99%
“…Caregiver education about hydrocephalus is considered essential in preventing significant morbidity and even mortality due to shunt failure. 1,17 The Internet is an evolving tool in caregiver/patient education. 2,8,9,14,19,25,26,31 In a bold statement in 1996, Pareras and Martin-Rodriguez 33 stated that "the Internet is dividing medical professionals, creating two kinds of people: those who take advantage of the benefits which the information era offers, and those who live in ignorance of these benefits."…”
mentioning
confidence: 99%